Analisa Pengaruh Kompensasi terhadap Kinerja Kerja Karyawan - Ernawati Ernawati; Arman Paramansyah; Suranto Suranto (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2020)
Lack of work performance is not without cause, but is influenced by many factors, one of which is compensation. At present the Indonesian government determines workers' compensation based on their respective regions, compensation which is determined based on the needs of decent living (KHL) in an area as stipulated dalam Undang-Undang No.13 tahun 2003 tentang Ketenagakerjaan , The purpose of this study was to determine whether there is an influence between compensation with work performance on the employees of the company The sample of this research is 32 employees who work are male and female employees. This study uses 2 measuring instruments, namely the compensation scale which amounts to 20 statement items with a reliability of 0.947 and a scale of work performance totaling 20 statements with a reliability of 0.896. Data were analyzed using simple regression using SPSS 21 for Window. The results showed t-hitung 7.216 while t-table 1.697 with degrees of freedom (df) = n-2 or 32-2 (n is the number of respondents) then the result was 7.216 with a level of significance (level of significance) using α = 5% or 0.05. The test found that tcount> ttable for compensation amounted to 7.216> 1.697, it can be concluded Ha was accepted, meaning that there was a significant influence between compensation on employee work performance at PT. Mulia bersaudara. The value of r (Correlation Coefficient) obtained was 0.797 and the value of r2 (Determination Coefficient) was 0.634.